Analysis of Australian tourism, hospitality and events undergraduate education programs : issues paper no.4. - Dredge, Dianne; Benckendorff, Pierre; Day, Michele; Gross, Michael J.; Walo, Maree; Weeks, Paul; Whitelaw, Paul A. (Office for Learning and Teaching, 2012)
This issues paper emanates from a project that clarified what constitutes tourism and hospitality (TH) education in the Australian higher education environment. This was achieved by mapping TH curriculums, including core knowledge and skill requirements, and pathways through the curricular space. This project involved an analysis of current programs in the Australian TH education environment. Data was collected from university managers, students, educators and employers about the future of TH education, core knowledge and skills, and the ideal balance between liberal and vocational education in higher TH education. The outcomes of this project :(1) informed strategic decision-making within universities about TH education, (2) provided practical level guidance about curriculum renewal to program coordinators and administrators, and to those dealing with articulations admissions, credit applications, and partnership arrangements with other universities and education providers, (3) informed curriculum content, graduate skills, and knowledge requirements, and (4) informed discussions about TH accreditation.